Effect of three different chin‐down maneuvers on Swallowing pressure in healthy young adults. (12th August 2015) - Matsubara, Keigo; Kumai, Yoshihiko; Kamenosono, Yuta; Samejima, Yasuhiro; Yumoto, Eiji
Abstract : Objectives/Hypothesis: To determine the effects of three different chin‐down maneuvers on swallowing pressure (SP) in healthy young adults using high‐resolution manometry (HRM). Study Design: Repeated measures with subjects serving as their own controls. Methods: Twenty‐six healthy subjects (average age 26.4 [range 21–35] years) swallowed 5 mL of cold water to examine the maximum swallowing pressure (MSP) at the velopharynx, meso‐hypopharynx, and upper esophageal sphincter (UES), and to determine the duration of lowered SP at the UES using HRM. The subjects swallowed in the neutral position as a control and in the following three chin‐down positions: 1) head flexion (HF); 2) neck flexion (NF); and 3) combined head and neck flexion (HFNF). Results: The MSP at the velopharynx and meso‐hypopharynx did not significantly differ among the three chin‐down positions. Upon swallowing in the NF posture, the MSP was significantly lower ( P < 0.0001) at the UES, and the duration of the lowered SP at the UES was significantly prolonged ( P = 0.0010) compared to the neutral position. In comparison, the duration of lowered SP at the UES was significantly ( P = 0.0001) shorter in the HF position than in the neutral position. Moreover, the HFNF position significantly ( P = 0.0276) lowered the MSP at the UES compared to the control position. Conclusion: In young healthy adults, NF maneuver resulted in significantly lower MSP and longer duration of the lowered swallowing pressure at the UES, which might assist bolus passage through the UES. Level of Evidence: 3b. Laryngoscope, 126:437–441, 2016